AeMOPE-1, a Novel Salivary Peptide From Aedes aegypti, Selectively Modulates Activation of Murine Macrophages and Ameliorates Experimental Colitis - Lara, Priscila G.; Esteves, Eliane; Sales-Campos, Helioswilton; Assis, Josiane B.; Henrique, Maressa O.; Barros, Michele S.; Neto, Leila S.; Silva, Pedro I.; Martins, Joilson O.; Cardoso, Cristina R. B.; Ribeiro, José M. C.; Sá-Nunes, Anderson (Frontiers in Immunology, 2021)
The sialotranscriptomes of Aedes aegypti revealed a transcript overexpressed in female salivary glands that codes a mature 7.8 kDa peptide. The peptide, specific to the Aedes genus, has a unique sequence, presents a putative secretory nature and its function is unknown. Here, we confirmed that the peptide is highly expressed in the salivary glands of female mosquitoes when compared to the salivary glands of males, and its secretion in mosquito saliva is able to sensitize the vertebrate host by inducing the production of specific antibodies. The synthetic version of the peptide downmodulated nitric oxide production by activated peritoneal murine macrophages. The fractionation of a Aedes aegypti salivary preparation revealed that the fractions containing the naturally secreted peptide reproduced the nitric oxide downmodulation. The synthetic peptide also selectively interfered with cytokine production by murine macrophages, inhibiting the production of IL-6, IL-12p40 and CCL2 without affecting TNF-alpha or IL-10 production. Likewise, intracellular proteins associated with macrophage activation were also distinctively modulated: while iNOS and NF-kappaB p65 expression were diminished, COX-2 and p38 MAPK expression did not change in the presence of the peptide. The anti-inflammatory properties of the synthetic peptide were tested in vivo on a dextran sulfate sodium-induced colitis model. The therapeutic administration of the Ae. aegypti peptide reduced the leukocytosis, macrophage activity and nitric oxide levels in the gut, as well as the expression of cytokines associated with the disease, resulting in amelioration of its clinical signs. Given its biological properties in vitro and in vivo, the molecule was termed Aedes-specific MOdulatory PEptide (AeMOPE-1). Thus, AeMOPE-1 is a novel mosquito-derived immunobiologic with potential to treat immune-mediated disorders.